2016
DOI: 10.1016/j.molstruc.2015.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical analysis of (+)-limonene using theoretical and experimental NMR and chiroptical data

Abstract: a b s t r a c tUsing limonene as test molecule, the success and the limitations of three chiroptical methods (optical rotatory dispersion (ORD), electronic and vibrational circular dichroism, ECD and VCD) could be demonstrated. At quite low levels of theory (mpw1pw91/cc-pvdz, IEFPCM (integral equation formalism polarizable continuum model)) the experimental ORD values differ by less than 10 units from the calculated values. The modelling in the condensed phase still represents a challenge so that experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 82 publications
2
16
0
Order By: Relevance
“…As for the basis set, we recommend Ahlrichs’ def2‐SVP or def2‐TZVP, or, more in general, basis sets of double or triple‐ζ quality with a sufficiently wide set of polarization functions. Diffuse functions may be necessary whenever Rydberg states contribute substantially to the ECD spectrum . The basis set convergence may be easily verified by using one of the two methods discussed in the paragraph “Choice of the TDDFT Basis Set” below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the basis set, we recommend Ahlrichs’ def2‐SVP or def2‐TZVP, or, more in general, basis sets of double or triple‐ζ quality with a sufficiently wide set of polarization functions. Diffuse functions may be necessary whenever Rydberg states contribute substantially to the ECD spectrum . The basis set convergence may be easily verified by using one of the two methods discussed in the paragraph “Choice of the TDDFT Basis Set” below.…”
Section: Resultsmentioning
confidence: 99%
“…Diffuse functions may be necessary whenever Rydberg states contribute substantially to the ECD spectrum. 37 The basis set convergence may be easily verified by using one of the two methods discussed in the paragraph "Choice of the TDDFT Basis Set" below. In general, the weaker the computed (and experimental) ECD spectrum, the stronger will be its dependence on the calculation method, including functional, basis set, input geometry, and solvation model.…”
Section: Results and Discussion A Typical Computational Flowchartmentioning
confidence: 99%
“…Firstly, the UV-vis and CD spectra of nBuPS aggregates produced in a mixture of [62]. Although vibrational circular dichroism (VCD) experiment followed by population analysis of neat (S)-limonene was not reported by the same research groups [62,63], these results prompted us to investigate the g abs value of nBuPS aggregates in detail. Noting that (R)-limonene is a naturally abundant terpene, while (S)-limonene is not.…”
Section: Uv-vis and CD Characteristics Of Diarylpolysilane Aggregatesmentioning
confidence: 99%
“…Possibly, each dot weakly emits the CPL signal because of the CPL-active nBuPS aggregates. The g abs value of nBuPS aggregates vs (R)-and (S)-limonene fractions in tersolvents Recent knowledge and understanding of the conformational structure indicated that (R)-limonene mainly exists as a mixture of three stable rotational isomers with the quasi-equatorial orientation of the isopropenyl group on the cyclohexene ring[62,63]. Minor rotational isomers are three unstable isomers with the quasi-axial orientation of the isopropenyl group on the cyclohexene ring…”
mentioning
confidence: 99%
“…Since a few decades, ab initio NMR chemical shift calculations have been used to interpret experimental spectroscopic data and therefore to assign the structures, the stereostructures, as well as the conformations of complex molecules, including, to name a few, supramolecular host-guest compounds [1], elatenyne [2], eightmembered benzoannulated lactams [3], hexahydrobenzazocines [4], strychnine [5], heparin trisaccharide [6], triterpenes [7], dimeric indole alkaloids [8], thiazole and selenazole derivatives [9], (þ)-limonene [10], darcyribeirine [11]. This approach has also helped to analyze the signatures of stereochemistry in poly(vinyl chloride) (PVC) oligomers and to highlight the signatures of their unsaturated and branched defects [12,13].…”
Section: Introductionmentioning
confidence: 99%